Psychological Contract and Quality of Organizational Life: An Empirical Study on Workers at a Rest Home - Battisti, Martina; Fraccaroli, Franco; Fasol, Rino; Depolo, Marco (Relations industrielles / Industrial Relations, 2007)
This study assesses psychological contract using a feature-oriented approach which measures perceptions about employer and employee obligations along the dimensions of duration, tangibility, scope, stability/flexibility, contract level and exchange symmetry. Questionnaires were administered to 170 workers (23 males, 147 females) employed at a rest home in Northern Italy. The results confirm the hypothesized relation between the employee’s perceptions of employer obligations and the organizational role component of organizational life (in terms of low role ambiguity and high development expectations). Similarly, the hypothesized relation between the employee’s perceived obligations to the employer and the affective and motivational area is supported (in terms of affective commitment and perceived organizational justice). The results also show the importance of assessing the employee’s perceptions both of employer obligations and of her/his own obligations to the employer, considering the differentiated influence that each of them has on organizational life.